RECONSTRUCTION OF A LOST CARBONATE FACTORY BASED ON ITS BIOGENIC DETRITUS (TERNATE-TRAVEDONA FORMATION AND GONFOLITE LOMBARDA GROUP - NORTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2016)
This work reconstructs a now completely eroded late Eocene to earliest Oligocene carbonate factory of Northern Italy, through the analysis of a carbonate deep-water-fan sequence (Ternate-Travedona Formation) and the limestone detritus dispersed into the late Oligocene clastic-wedge of the Gonfolite Lombarda Group. Textural characteristics and skeletal assemblages of the Gonfolite pebbles were studied and compared to those of the Ternate-Travedona Formation. The same skeletal assemblage and the same taxa were found in samples from both areas, suggesting their common origin. Whereas the Ternate-Travedona Formation skeletal grains were reworked during transport, the Gonfolite Lombarda Group pure-limestone pebbles are pristine fragments of the carbonate platform, that was uplifted and eroded from the late Eocene to the early Oligocene. Using both these sources of information it was possible to reconstruct the late Eocene environment and its facies distribution. The areas undergoing high hydrodynamic energy were dominated by free-living coralline-algal branches, rhodoliths and larger thick-tested benthic foraminifera. A coralline framework, associated with thin-tested benthic foraminifera and boxwork rhodoliths, was present in slightly deeper and sheltered environments. Episodic debris flows, mainly triggered by river floods, supplied the sub-marine fan of the Ternate-Travedona Formation. These events were able to down-cut through the narrow platform and rip off large fragments of the substrate. River runoff probably also supplied large quantities of organic matter, leading to local oxygen-depletion and preservation of organic matter. The combined stressful effects of bottom instability and riverine discharge probably excluded corals from the association. The integrated study of the Ternate-Travedona Formation, and of the limestone pebbles in the Gonfolite Group, have enabled the reconstruction of this otherwise lost Eocene carbonate factory.